Teacher Misbehaviour and Its Impact on the Education of Students in Public Basic Schools: A Study of Teachers in the Tamale Metropolis - Ibrahim, Mohammed Gunu; Ibrahim, Kamil (Advances in Social Sciences Research Journal, 2022)
This study explores the causes, forms and effects of teacher misbehaviour on the educational progression of basic school level students in the Tamale Metropolis in the Northern Region of Ghana. The study employed the survey design and adopted a quantitative approach in analyzing the data. The findings revealed that absenteeism, drunkenness, sexual abuse, and drug abuse were forms of misbehaviour practised by some teachers in public basic schools in Tamale. Precipitating factors included poor living environment, inadequate salaries and teachers residing faraway from schools. Based on these findings, the research recommended that Ghana Education Service in the Tamale Metropolis should withdraw or sanction any teacher found to be engaging with the abuse of drugs and other substances. Headteachers of basic schools in the metropolis should be given more training on monitoring and effective observation of their teachers and on their relationship with the students, especially female students.